A precise measurement of the tau lepton lifetime - Abreu, P; Adam, W; Adye, T; Agasi, E; Ajinenko, I; Aleksan, R; Alekseev, G; Allport, P; Almehed, S; Alvsvaag, S; Amaldi, U; Amato, S; et al. (1996)
The tau lepton lifetime has been measured using three different methods with the DELPHI detector. Two measurements of one-prong decays are combined, accounting for correlations, giving a result ofττ = 291.8 ± 3.3 (stat.) ± 2.0(sys.) fs while the decay length distribution of three-prong decays gives the result ττ = 286.7 ± 4.9 (stat.) ± 3.3 (sys.) fs. Combining the results presented here with previous DELPHI measurements, we get ττ = 291.4 ± 3.0 fs and find that the ratio of the coupling constant for tau decay relative to that for muon decay is 0.990 ± 0.009, compatible with lepton universality.